Licensing Authority and Legal Certainty in Contemporary Administrative Law - Didi Nursidi (International Journal of Science Education and Cultural Studies, 2023)
In the implementation of modern administrative law, the authority to issue permits to regulate public space is inseparable from the individual's right to legal certainty in business and activities. In the context of contemporary state administrative law, the tension between the broad authority to issue permits held by government officials and the increasing demands for legal certainty from the public and business actors is an issue that has not been fully resolved, both theoretically and in policy implementation. This study aims to investigate the relationship between licensing authority and legal certainty from the perspective of contemporary state administrative law in Indonesia, identify structural factors that determine the quality of legal certainty in licensing governance, and formulate a normative and institutional framework capable of optimizing licensing authority as an instrument for creating legal certainty. The study uses a normative juridical approach with a comparative analysis of legal documents and a systematic and comprehensive library research method. The collection of legal materials is carried out through the study of primary legislation, judicial decisions, comparative administrative law doctrine, and internationally reputable scientific literature. The analysis is conducted using a layered normative analysis framework that integrates the dimensions of legality, proportionality, and legal certainty. The findings indicate that legal certainty in licensing authority in Indonesia is multidimensional and influenced by five structural factors: coherence of licensing regulations, clarity of authority boundaries, standardization of administrative procedures, legal protection mechanisms, and consistency in the application of norms by licensing bodies. This study produces a normative framework for legal certainty in licensing based on contemporary administrative law principles that can serve as a reference for licensing regulatory reform in Indonesia.